Predominant polarity in bipolar affective disorder and its impact on cognition and quality of life - Shashank Bhardwaj; Deoraj Sinha; Ami Pawar; Astik Mane (Indian Journal of Psychiatry)
Background: Bipolar mood disorder or bipolar affective disorder (BPAD) is a chronic illness characterized by phases of mania/hypomania, depression, or mixed episodes. The course of bipolar mood disorder is relapsing in nature. It is associated with high comorbidity rates, a large number of premature deaths due to suicide, and a worse social and work performance. All of those characteristics entail a significant economic impact due to both direct and indirect costs and require an effective diagnostic and therapeutic approach. Lifetime prevalence of BPAD is approximately 4% worldwide. Various attempts have been made to define “predominance” of polarity in BPAD. Need for this Study: Our study tries to highlight the existence of predominant polarity by comparing effects of the same on substance consumption, cognitive abilities, quality of life, and preponderance of specific polarity to specific gender. Method: After Institutional Ethics Committee Approval and written informed consent, patients who were diagnosed with BPAD attending out-patient department of a tertiary care hospital in Mumbai were recruited. A total of 57 participants were enrolled. The World Health Organization Quality of Life - Brief Scale (WHOQOL BREF) and the Montréal Cognitive Assessment (MoCA) were both used to evaluate the patients’ quality of life and cognitive ability, respectively. Discussion and Results: Men exhibited manic predominant polarity, while women had depressive predominant polarity, with P value of. 003. Regarding age, illness length, education, substance abuse, family history, and suicide attempts, there was no discernible difference in the polarities. The outcome of female bipolar patients may be improved if the clinician is mindful of the burden of depression, risk of misdiagnosis, and variable therapy response. Interestingly, our study found no significant difference between MoCA scores of those with depressive and manic polarity. Substantial MoCA score differences were found between the groups with depressive polarity and no polarity. Conclusion: Men were observed to experience more manic episodes. More women in the study experienced predominantly depressive polarity, highlighting the need to probe for a past history of hypomania or mixed episodes to avoid misdiagnosis as unipolar depression in them. Manic predominate polarity performed better in the physical and psychological domains of the post hoc test for quality-of-life BREF scale. There were substantial MoCA score differences between the groups with depressive polarity and no polarity, with the depressive polarity showing more cognitive decline.